Peningkatan Pengetahuan Pasien Tentang Diet Pasien Tuberkulosis di RSU IPI Medan - Nixson Manurung (Jurnal DIKMAS, 2024)
TB is one of the 10 causes of death and the primary cause of infectious agents in the world. Some of the influencing factors are behavioral factors, namely knowledge, attitude and behavior in the implementation of routine medication compliance. The method used was observational descriptive with 25 participants who were patients at Imelda Workers' Hospital in Medan. The PkM team provided the material in question: 1) Definition of tuberculosis disease, 2) health education about dietary fulfillment 3) how to regulate the diet of tuberculosis sufferers, 4) increasing knowledge and skills. After the implementation of the activity: 1) Definition of tuberculosis (TB) for the majority of good as many as 25 people, 2) health education about the fulfillment of the good majority diet for 20 people, 3) how to manage the diet of the majority of people with tuberculosis as many as 16 people, 4) improvement of knowledge of tuberculosis treatment for the majority of good as many as 21 people. The increase in knowledge and skills of participants is because the community has a great desire to treat and prevent dengue fever in family members at home.